An Investigation of the Relationship Between e-Health Literacy and Telerehabilitation Awareness, Knowledge, Attitudes, and Skills of Physiotherapists in Türkiye - Çelik, Erman Berk; Özaltın, Gülfem Ezgi; Aygül, Gökhan (The European Research Journal, 2026)
Objectives: The aim of this study was to determine the e-health literacy levels of physiotherapists in Türkiye and to examine their relationship with telerehabilitation awareness, knowledge, attitudes, and skills. Methods: This descriptive and cross-sectional study included 106 physiotherapists who participated through an online survey between January and March 2024. E-health literacy was evaluated using the E-Health Literacy Scale, while telerehabilitation competencies were assessed with the Telerehabilitation Awareness, Knowledge, Attitudes and Skills Scale. Statistical analyses were conducted using multiple regression and ordinal regression models. Results: The median e-health literacy score was 30 (min: 12-max: 40), the mean (±SD) was (28.79±6.44). A statistically significant relationship was found between e-health literacy and all subdimensions of telerehabilitation: awareness (η²ₚ=0.153, P<0.001), knowledge (η²ₚ=0.041, P=0.038), attitudes (η²ₚ=0.299, P<0.001), and skills (η²ₚ=0.178, P<0.001). E-health literacy explained 34.7% of the variance in these domains. Additionally, telerehabilitation awareness significantly predicted the frequency of telerehabilitation use (β=0.143, P<0.001). Conclusions: E-health literacy plays a critical role in the readiness of physiotherapists to adopt telerehabilitation practices. Educational programs aimed at improving digital literacy and awareness may enhance the effective integration and implementation of e-health and telerehabilitation services in physiotherapy.